The Effectiveness of Reading Aloud Application on the Ability to Read the QS. Al-Ma’un and Translations in English - Dian Pratiwi; Fatma Yuniarti; Siswoyo Siswoyo (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2023)
This research was conducted to find out how effective the application of the reading-aloud method is on the ability to read the Q.S Al Ma'un and its translation in English. This study aims to determine whether the reading-aloud method affects students' ability to read Q.S Al-Ma'un of the Quran and its English translation in the second semester of the Management Study Program at Muhammadiyah University of Pringsewu. This study employs a quasi-experimental methodology. The results showed that the experimental class's post-test score was 69.1, with a standard deviation of 8.22, and the practical class's pre-test score was 56.5, with a standard deviation of 8.53. The control class's post-test score was 60.40, with a standard deviation 9.68. The outcomes of the two tests are dissimilar. Additionally, both classes’-test results are 0.00. This indicates that the hypothesis is correct and that the reading-aloud strategy can help students become more proficient readers.